(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
The purpose of this article is to define the role of enterprise’s reserves to ensure the economic security of the enterprise. Given a goal of the study, defined objectives include: a definition of the economic security, a definition of economic security risks of the enterprise, their sources and targets. On the basis of this information, it defines the role of the company in the context of provision of the economic security.